2013
DOI: 10.1063/1.4812344
|View full text |Cite
|
Sign up to set email alerts
|

Coherent photon interference elimination and spectral correction in femtosecond time-resolved fluorescence non-collinear optical parametric amplification spectroscopy

Abstract: We report an improved setup of femtosecond time-resolved fluorescence non-collinear optical parametric amplification spectroscopy (FNOPAS) with a 210 fs temporal response. The system employs a Cassegrain objective to collect and focus fluorescence photons, which eliminates the interference from the coherent photons in the fluorescence amplification by temporal separation of the coherent photons and the fluorescence photons. The gain factor of the Cassegrain objective-assisted FNOPAS is characterized as 1.24 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Here we test that principle for broadband fluorescence upconversion spectroscopy (FLUPS). [4][5][6][7] Fluorescence gating has been performed with a Kerr shutter, [8][9][10][11][12][13][14][15] by non-collinear optical parametric amplification [16][17][18][19][20] or by diffraction from a transient grating, 21 in addition to broadband upconversion schemes. [4][5][6][7][22][23][24][25] Here we consider only reports where spontaneous emission from molecular or similar sources is gated, dispersed, and registered simultaneously at all relevant wavelengths with a view to obtain true molecular spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Here we test that principle for broadband fluorescence upconversion spectroscopy (FLUPS). [4][5][6][7] Fluorescence gating has been performed with a Kerr shutter, [8][9][10][11][12][13][14][15] by non-collinear optical parametric amplification [16][17][18][19][20] or by diffraction from a transient grating, 21 in addition to broadband upconversion schemes. [4][5][6][7][22][23][24][25] Here we consider only reports where spontaneous emission from molecular or similar sources is gated, dispersed, and registered simultaneously at all relevant wavelengths with a view to obtain true molecular spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed description of the FNOPAS technique has been reported in Ref. [18]. For CDSB nano-wires, the SH of the fundamental beam is used as excitation pulses.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence non-collinear optical parametric amplification spectroscopy is a newly developed technique for recording ultrafast time-resolved broadband fluorescence spectra. [17][18][19][20][21] The proof-in-principle experiment was demonstrated by Fita et al in the visible range. 17 Soon after, our group extended the seeding fluorescence to the near IR region, 18 and the fluorescence decay kinetics together with the time-resolved spectra can be obtained by its conjugated part in the visible region.…”
Section: Introductionmentioning
confidence: 93%
“…Later, we reported a gain factor of 10 5 -10 6 , 19 a detection limit of about 20 photons/pulse for noncoherent seeding light, 19,22 and a single photon/pulse for coherent seeding light 23 for a 120 fs pulsed laser, spectral correction method by using the inherent spectrum of the vacuum quantum noise which would be amplified as the superfluorescence concomitant with the amplified fluorescence, 20 and Cassegrain objective for fluorescence collection to remove the possible interference from the white light continuum generation. 21 It has been reported that the amplified signal of non-collinear optical parametric amplification (NOPA) could be tuned from 460 to 1150 nm in a signal branch, the corresponding tuning range for the idler beam would be 600 nm to 2800 nm. 24 And we have shown that the bandwidth of more than 100 nm (2500 cm −1 ) with a relatively uniform gain curve (normalized value in the range of 0.8-1.0) could be achieved at a fixed phase-matched angle.…”
Section: Introductionmentioning
confidence: 99%